Impact of Atrial Fibrillation on the Outcomes after MitraClip®: A Meta-Analysis. Issue 6 (2nd November 2018) - Megaly, Michael; Abraham, Bishoy; Saad, Marwan; Omer, Mohamed; Elbadawi, Ayman; Tawadros, Mariam; Khalil, Charl; Nairoz, Ramez; Almomani, Ahmed; Sengupta, Jay; Kalra, Ankur; Brilakis, Emmanouil; et al.
ABSTRACT: Background: Atrial fibrillation (AF) has been associated with worse outcomes in patients undergoing mitral valve surgery for mitral regurgitation. The impact of preexisting AF on the outcomes after transcatheter mitral valve repair with MitraClip® (Abbott Vascular, Santa Clara, CA, USA) has not been well studied. Methods: An electronic search was performed until December 2017 for studies reporting outcomes after MitraClip® in patients with AF versus those with no AF. Outcomes of interest included all-cause mortality, stroke and major adverse cardiovascular events (MACE) defined as the composite outcome of death, stroke, and myocardial infarction at the longest follow-up reported. Results: A total of four studies including 1473 patients (AF n = 697; no AF n = 776) were included. There was no difference in procedural success or procedural time between patients with AF versus those without AF. AF was associated with increased mortality after MitraClip® compared with patients with no AF (OR 1.54, 95% CI (1.16, 2.04), p  = 0.003, I 2  = 0%) over a mean follow-up period of 10.2 months. In a sensitivity analysis excluding early postoperative (30-day) outcomes, AF remained associated with higher mortality (OR 1.53, 95% CI (1.15, 2.03), p  = 0.003, I 2  = 19%). AF was associated with a higher incidence of MACE after MitraClip® (OR 1.46, 95% CI (1.03, 2.07), p  = 0.03, I 2  = 13%). No difference was observed in the risk of stroke between patients with versus without AF after MitraClip® (OR 1.13, 95%CI (0.36, 3.56), p  = 0.84, I 2  = 37%). Conclusions: Compared with patients without AF, patients with preexisting AF are at higher risk of death and MACE after MitraClip®.